Appetite and energy intake responses to acute energy deficits in females versus males - Nawal Alajmi; Kevin Deighton; James King; Alvaro Reischak-Oliveira; Lucy K. Wasse; Jenny Jones; Rachel L. Batterham; David Stensel (2016)
PURPOSE: To explore whether compensatory responses to acute energy deficits induced by exercise or diet differ by sex. METHODS: In experiment one, twelve healthy women completed three 9 h trials (control, exercise-induced (Ex-Def) and food restriction induced energy deficit (Food-Def)) with identical energy deficits being imposed in the Ex-Def (90 min run, ∼70% of VO2 max) and Food-Def trials. In experiment two, 10 men and 10 women completed two 7 h trials (control and exercise). Sixty min of running (∼70% of VO2 max) was performed at the beginning of the exercise trial. Participants rested throughout the remainder of the exercise trial and during the control trial. Appetite ratings, plasma concentrations of gut hormones and ad libitum energy intake were assessed during main trials. RESULTS: In experiment one, an energy deficit of ∼3500 kJ induced via food restriction increased appetite and food intake. These changes corresponded with heightened concentrations of plasma acylated ghrelin and lower peptide YY3-36. None of these compensatory responses were apparent when an equivalent energy deficit was induced by exercise. In experiment two, appetite ratings and plasma acylated ghrelin concentrations were lower in exercise than control but energy intake did not differ between trials. The appetite, acylated ghrelin and energy intake response to exercise did not differ between men and women. CONCLUSIONS: Women exhibit compensatory appetite, gut hormone and food intake responses to acute energy restriction but not in response to an acute bout of exercise. Additionally, men and women appear to exhibit similar acylated ghrelin and PYY3-36 responses to exercise-induced energy deficits. These findings advance understanding regarding the interaction between exercise and energy homeostasis in women.